2010
DOI: 10.1038/nsmb.1947
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Rif2 and lack of Mec1 target short telomeres for elongation rather than double-strand break repair

Abstract: S. cerevisiae telomerase binds and preferentially elongates short telomeres, events that require the checkpoint kinase Tel1. We show that the Mre11 complex bound preferentially to short telomeres, which can explain the preferential binding of Tel1 to these ends. Compared to wild type length telomeres, short telomeres generated by incomplete replication had low levels of the telomerase inhibitory protein Rif2. Moreover, in the absence of Rif2, Tel1 bound equally well to short and wild type length telomeres, arg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
81
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(87 citation statements)
references
References 56 publications
(90 reference statements)
6
81
0
Order By: Relevance
“…7D), although RIF1 deletion had a more modest effect than RIF2 deletion in allowing telomere addition (Fig. 7D) (26,37).…”
Section: Resultsmentioning
confidence: 99%
“…7D), although RIF1 deletion had a more modest effect than RIF2 deletion in allowing telomere addition (Fig. 7D) (26,37).…”
Section: Resultsmentioning
confidence: 99%
“…We concluded that telomeres can be maintained by telomerase alone in sae2D sgs1D cells, but recombination also contributes to elongate telomeres in these cells. We next asked whether telomerase activity is sensitive to the negative regulation by Rif2, which competes with Tel1 binding at telomeres 27,44 , in the combined absence of Sae2 and Sgs1. We monitored the telomere length of sae2D sgs1D rif2D clones as described in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…29,37,38 Like RPA, ATR and its yeast homolog Mec1 were both found to bind telomeres transiently during the cell cycle. 29,31 These findings suggest that the competition between RPA and POT1 on telomeric ssDNA may not be a simple one. Furthermore, the interplay between RPA and POT1 may be important for the coordination of telomere replication and telomere capping during the cell cycle.…”
mentioning
confidence: 87%
“…Indeed, in both yeast and humans, RPA was found to transiently associate with telomeres during S phase. [28][29][30][31] Furthermore, genetic studies in yeast have clearly implicated RPA in telomere maintenance. [32][33][34][35][36] While persistent activation of ATR at telomeres would likely trigger cell cycle arrest, senescence or apoptosis, ATR is also known to play a positive role in telomere maintenance.…”
mentioning
confidence: 99%